Leadership Coaching and the Myth of the Rational Client - Forbes, Raymond L. (Advances in Social Sciences Research Journal, 2023)
This paper will address the issue of whether or not the clients of leadership coaches think and act in completely rational ways. It explores the question using a lens derived from the fields of Behavioral Economics and the Brain Sciences. Beginning with a look at the origins of the idea of rationality, this work proceeds to consider what’s really at issue, why it matters, and the possible trap posed by assuming strong client rationality. The paper concludes by posing options for resolution of the rationality myth by exploring the concepts of heuristics, bias, anchoring and priming. The paper concludes with suggestions for what leadership coaches can actually do to improve their work with clients and a short summary of the main ideas.